Performance of Responsive Powder Concrete with Ultra Fine Mineral Admixtures: Enhancing the Short-term Strength and Durability of Responsive Powder Concrete using Ultra Fine Mineral Admixtures (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The goal of this study is to find practical ways to increase the RPC concrete's short-termstrength without increasing costs. Research on the effects of increasing the fineness of the mineraladmixtures on the short-term strength of concrete was conducted. Instead of using more expensive nanosized mineral admixtures, common mineral admixtures like silica fume and metakaolin were employed,but ground down to an ultra-fine size. To decrease the amount of cement used and, more importantly, toimprove the strength from regular too high, supplementary cementitious elements (pozzolans) arecombined with cement. These pozzolanic admixtures provide concrete with increased durability anddecreased brittleness. Increases in the fineness of the pozzolans were attempted to improve the shorttermstrength, and substantial effort was made to include waste utilization into the concrete. It wasshown that specimens with unground mineral admixtures were more resistant to a hostile environmentthan those with ground mineral admixtures. Whether ground or unground, specimens with MK addeddemonstrated superior strength and durability.